Sustainable HVAC Project Management: Strategies for Green Building Certification (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
The growing global focus on environmental sustainability has significantly increased the demand for energy-efficient and eco-friendly building systems. Heating, Ventilation, and Air Conditioning (HVAC) systems are central to a building’s energy consumption and environmental impact. This research explores sustainable HVAC project management strategies that align with green building certification standards, including Leadership in Energy and Environmental Design (LEED), Building Research Establishment Environmental Assessment Method (BREEAM), and WELL. It emphasizes integrating sustainability principles into the design, installation, and operation of HVAC systems to reduce energy consumption, lower greenhouse gas emissions, and enhance indoor environmental quality. Through a comprehensive review of current literature, case studies, and industry best practices, this study identifies effective project management methodologies that optimize HVAC system performance while meeting green certification requirements. It explores lifecycle cost analysis, energy modelling, the integration of renewable energy sources, and the use of smart technologies, such as IoT-enabled HVAC controls, for real-time energy monitoring and efficiency optimization. The research also addresses key challenges, including budget constraints, technical complexities, and balancing energy efficiency with occupant thermal comfort. The findings present a strategic framework for project managers, engineers, and sustainability consultants to implement effective HVAC solutions that support green building certifications. This framework bridges the gap between sustainable design goals and practical execution, reinforcing HVAC project management’s vital role in promoting environmentally responsible construction practices.
Keywords: HVAC; project management; energy efficiency; lifecycle cost analysis; renewable energy